2021
DOI: 10.3389/fgene.2021.793894
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prenatal Screening Based on Second-Trimester Ultrasonographic Soft Markers in Low-Risk Pregnant Women

Abstract: Background: We aimed to assess the clinical application of noninvasive prenatal screening (NIPS) based on second-trimester ultrasonographic soft markers (USMs) in low-risk pregnant women.Methods: Data of pregnant women between April 2015 and December 2019 were retrospectively analyzed. Pregnant women [age at expected date of confinement (EDC) of <35 years; low risks for trisomy 21 (T21) and trisomy 18 (T18) based on maternal serum screening; presenting second-trimester USMs (7 types)] who successfully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In addition, the proportion of various types of USM in the study population was also different; EIF accounted for 23.72% in a previous study [12], whereas in our study, EIF was the most frequent USM (81.71%). We have previously reported [20] that the incidence and PPV of NIPS for aneuploidy in fetuses with EIF were signi cantly low, which was con rmed here.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the proportion of various types of USM in the study population was also different; EIF accounted for 23.72% in a previous study [12], whereas in our study, EIF was the most frequent USM (81.71%). We have previously reported [20] that the incidence and PPV of NIPS for aneuploidy in fetuses with EIF were signi cantly low, which was con rmed here.…”
Section: Discussionsupporting
confidence: 87%
“…This may be because the population included in our study was predominantly young (below the age of 35 years at the expected date of con nement), while there were 9.37% pregnant women of an advanced maternal age in previous studies [12]. According to the relevant regulations (Article 20 of the Measures for the Implementation of Law of the Peoples Republic of China on Maternal and Infant Health Care (promulgated on June 20, 2001) ), prenatal diagnosis is often recommended for pregnant women in China who are at high risk based on maternal serum screening [20,21], advanced maternal age and fetuses with structural abnormalities, therefore, the risk of potential chromosomal aberrations was higher in those studies [12,19]. In addition, the proportion of various types of USM in the study population was also different; EIF accounted for 23.72% in a previous study [12], whereas in our study, EIF was the most frequent USM (81.71%).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the elevated incidence of EICF, its predictive value for chromosome abnormalities remains notably low, aligning with findings from previous studies. 18 Initially, EICF was found to be associated with a heightened risk of Down Syndrome. 19 However, contemporary research has indicated that isolated EICF does not increase the risk of aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies [18,19,22,27,31,32,[34][35][36][37] reported chromosomal abnormalities and the rate of abnormalities was 1.98% (range 0-5.7%) among those with EIF. The chromosomal abnormalities identified with EIF were Trisomy 18, 46, 21 XXY, XYY and Turner's syndrome.…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%